No easy harvest the dilemma of agriculture in underdeveloped countries - Millikan, Max F. (Little, Brown, 1967)
A revision and extension of the report of the Conference on Productivity and Innovation in Agriculture in the Underdeveloped Countries, held at Dedham, Massachusetts, from June 29 through August 7, 1964.